Heterogeneity of opinion, shareholder retention ratio and lockup period: Malaysian evidence - Albada A.; Soo-Wah L.; Yong O.; Nassir A.M.; Kamarudin F.; Anwar N.A.M. (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS/MYCITE